PENINGKATAN PEMBELAJARAN LOMPAT JAUH MELALUI PENDEKATAN BERMAIN PADA SISWA KELAS V SD NEGERI 025 KOTO SENTAJO - Jospiah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
The background of this research is the low ability of long jump student of grade V of SD Negeri 025 Koto Senjato, from 45 students only 19 students (42,22%) reaching KKM, mean student average is 56,40. This study is a classroom action research that aims to improve students' long jump skills with a play approach. This research was conducted at SD Negeri 025 Koto Senjato, the subject of this research is the students of class v with the number of 45 students. This research was conducted in two cycles with four stages, namely: planning, implementation, observation, and reflection. The result of the research stated that after applied the play approach, the students' ability in the race far has increased in the prasiklus the total number of students who completed is 19 students (42.22%) with the average value of 56.40. In the first cycle has increased with the number of 27 students (60.00%) with an average value of 68.80. And in the second cycle has increased with the number of 38 students (84.44%) with an average value of 76.40. Based on the results of this study, it can be concluded that the play approach can improve the ability of long jump student of grade V of SD Negeri 025 Koto Senjato